Avaliação do impacto de problemas bucais na qualidade de vida de técnicos e enfermeiros hospitalares - Barbosa, Julia Saraiva de Almeida (2022)
Objective: to evaluate the impact of oral problems on the quality of life of a hospital nursing team and its association with sociodemographic variables and stress. Methods: Cross-sectional study with a random sample of 111 nurses and nursing technicians from a university hospital. Three questionnaires were applied: Oral Health Impact Profile (OHIP-14), sociodemographic questionnaire and Bianchi Stress Scale. Fischer's exact test (p<0.05) found associations between each independent variable and the dimensions of the OHIP-14. To verify the strength of this association between event and exposure, the odds-ratio (OR) was calculated. To know the association between all the combined dimensions of the OHIP-14 (total score), with the independent variables, the Mantel-Haenzsel method was used, through the combined OR. Results: The prevalence of the impact of oral problems on quality of life was 51.4%. The dimensions with the greatest impact of oral problems were physical pain (37.8%) and psychological discomfort (35.1%), followed by physical disability (27.9%), psychological disability (26.1%), disability (18 .9%), functional limitation (15.3%) and social disability (11.7%). A higher frequency of oral health impact on quality of life was observed in individuals over 50 years of age (OR= 5.769, 95%CI= 1.806;18.431), single, widowed and divorced (OR= 2.396, 95%CI= 1.075;5.340), individuals with up to 12 years of schooling (OR= 2.766, 95%CI= 1.159;6.597), nursing technicians (OR= 4.073, 95%CI= 1.827;9.077) and individuals with up to 5 minimum wages (OR= 2.353, 95%CI = 1.080;5.127). In the relationship between stress and the impact of oral health, there was statistical significance in the dimensions disability (p=0.021), social disability (p=0.022) and psychological disability (p=0.045). Conclusion: Oral health conditions impact the quality of life of the hospital nursing team. Nursing technicians were more likely to have an impact on all dimensions that can be influenced by factors such as age, marital status, years of schooling, salary income and stress.